2016
DOI: 10.1111/jgs.14130
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve and Postoperative Delirium in Older Adults

Abstract: Background Higher cognitive reserve is reported to reduce risk of dementia. However, its role in reducing delirium risk is not well established. Objectives To examine the role of cognitive reserve on reducing delirium incidence and severity in older surgical patients. Design Prospective cohort study. Setting and Participants 142 older adults (mean age 71.2 y, 65% women) undergoing elective orthopedic surgery. Measurements Incidence (assessed by Confusion Assessment Method) and severity (Memorial Deliri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 31 publications
4
38
0
1
Order By: Relevance
“…Our dementia-free cohort allowed us to test the reserve hypothesis for delirium while minimizing the potential for confounding by pre-existing dementia. Although the relationship between reserve and postoperative delirium has been reported previously [15, 16, 47, 48], the formal test of the reserve hypothesis demonstrating effect modification between pathology and postoperative delirium -- has not been tested previously. The evidence for the existence of effect modification in our study may form the basis of future studies elucidating the role of reserve in delirium.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Our dementia-free cohort allowed us to test the reserve hypothesis for delirium while minimizing the potential for confounding by pre-existing dementia. Although the relationship between reserve and postoperative delirium has been reported previously [15, 16, 47, 48], the formal test of the reserve hypothesis demonstrating effect modification between pathology and postoperative delirium -- has not been tested previously. The evidence for the existence of effect modification in our study may form the basis of future studies elucidating the role of reserve in delirium.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Detailed information regarding results of patient recruitment and screening and reasons for exclusion have been previously reported. 19 A total of 155 subjects were enrolled. Of the subjects, eight withdrew prior to their surgery, two had their surgery canceled, and three were lost to followup.…”
Section: Resultsmentioning
confidence: 99%
“…(continued on next page) age-adjusted multivariate analysis on patients with a Mini-Cog© score less than or equal to 2 and showed they were more likely to develop POD with an odds ratio of 4.52 (95% 1.30-15.68, P = 0.05). Tow et al measured delirium using Confusion Assessment Method (CAM) and severity Memorial Delirium Assessment Scale (MDAS) to assess for postoperative delirium [12]. The results demonstrated that MMSE scores between 24 and 27 were associated with delirium incidence.…”
Section: Association Of Cognitive Impairment With In-hospital Outcomesmentioning
confidence: 99%